Chief Executive Officer (CEO) Power, CEO Keluarga, Dan Nilai IPO Premium Perusahaan Keluarga Di Indonesia - I Made Sudana; Ni Putu Nina Aristina (Jurnal Akuntansi, 2017)
he development of family firms led to increase the funding requirement forexpansion. Family firms can obtain funds from capital market by doing initial publicoffering (IPO). The aims of this research is to know the influence of CEO power usingproxy of CEO voting right, CEO tenure, and CEO interlock on IPO premium, and theinfluence of family CEO on IPO premium. This research uses 65 samples of family firm inIndonesia during 2001-2014. The result of multiple regression showed that CEO votingright, CEO interlock, and family CEO are positive significantly affect IPO premium. Thisfinding reveal that when investors make investment decision on IPO’s firms, they willevaluate the quality of firm’s CEO. Also, the presence of family CEO increase investor’svaluation on company shares that increase IPO premium.